Erbium- and ytterbium-doped sol-gel SiO2-HfO2 crack-free thick films onto silica on silicon substrate - Sigoli, Fernando A.; Goncalves, Rogeria R.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2006)
Aware of the difficulties in applying sol-gel technology on the preparation of thin films suitable for optical devices, the present paper reports on the preparation of crack-free erbium- and ytterbium-doped silica: hafnia thick films onto silica on silicon. The film was obtained using a dispersion of silica-hafnia nanoparticles into a binder solution, spin-coating, regular thermal process and rapid thermal process. The used methodology has allowed a significant increase of the film thickness. Based on the presented results good optical-quality films with the required thickness for a fiber matching single mode waveguide were obtained using the erbium- and ytterbium-activated sol-gel silica:hafnia system. The prepared film supports two transversal electric modes at 1550 nm and the difference between the transversal electric mode and the transversal magnetic mode is very small, indicating low birefringence. Photoluminescence of the I-4(13/2) -> I-4(15/2) transition of erbium ions shows a broad band centered at 1.53 mu m with full width at a half maximum of 28 nm. Up-conversion emission was carried out under different pump laser powers, and just one transition at red region was observed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: spin coating; luminescence; silica; sol-gels (xerogels)